The Effects of Increasing Organic or Inorganic Zinc on Growth Performance and Carcass Characteristics of Finishing Pigs - E. W. Stephenson; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 3,390 pigs (PIC 337 × 1050; initially 63.2 lb), housed in three replicate barns, were used in this study to determine the influence of increasing organic or inorganic Zn sources on growth performance and carcass characteristics of finishing pigs. A total of 126 pens of pigs were allotted to 1 of 7 dietary treatments, with 24 to 27 pigs per pen and 14 to 17 replications per treatment. All diets contained a trace mineral premix that provided 55 ppm of Zn from ZnSO4. The seven experimental treatments were a control diet with no additional zinc included in the diet; the control diet with an additional 25, 50, or 75 ppm of Zn from a zinc AA complex (ZnAA; Availa®-Zn; Zinpro Corporation, Eden Prairie, MN); or the control diet with an additional 25, 50, or 75 ppm of zinc from ZnO. Diets were fed in meal form, for five dietary phases, and formulated to maintain a constant standardized ileal digestible Lys:NE ratio within phase. Overall, a Zn × level interaction (quadratic; P<0.05) was observed for ADG as pigs fed increasing ZnO had similar ADG, while pigs fed added levels of 25 and 50 ppm ZnAA had decreased performance compared to those fed the highest level of ZnAA. A Zn source × level interaction (quadratic; P<0.05) was also observed for overall F/G. This was due to pigs fed diets with 25 or 50 ppm Zn from ZnAA having poorer F/G compared to pigs fed similar levels of ZnO. The interaction in ADG also led to a tendency (quadratic; P<0.10) for a Zn source × level interaction for final BW. No differences were observed for ADFI. For carcass characteristics, a Zn source × level interaction (P<0.05) was observed for HCW, as pigs fed diets with 25 or 50 ppm Zn from ZnAA had decreased HCW compared with those fed 75 ppm Zn from ZnAA, while increasing ZnO did not influence HCW. Loin depth and percentage lean tended to increase and then decrease (quadratic; P<0.10) as added ZnAA increased; however, a similar response was not observed for increasing added ZnO. These data suggest that in finishing pigs, supplemental ZnO did not impact growth performance, but low inclusion levels of ZnAA increased F/G and reduced final BW.
Keywords: finishing pigs; growth; zinc